Characterization of Listeria monocytogenes isolated from foods / Zuraini Mat Issa, Maimunah Mustakim and Son Radu - Mat Issa, Zuraini; Mustakim, Maimunah; Radu, Son (Research Management Institute (RMI), 2012)
Listeria monocytogenes is one of the major food-borne pathogen with an opportunistic character that is able to cause severe human listeriosis worldwide. The development of a surveillance and detection system concerning food safety in this country needs to be improved. Therefore, this study was conducted to provide a general baseline on the contamination of L. monocytogenes in various foods in the local markets in Selangor. A total of 140 raw and ready-to-eat food samples were analyzed by plating on selective PALCAM medium and the suspected L. monocytogenes colonies were confirmed at molecular level by MPN-PCR technique using primers specific for this food-borne pathogen. All of the 23 isolated strains yield a PCR product of 938 bp and 701 bp for 16s rRNA gene and hylA virulence gene respectively. The confirmed isolates were characterized for their intra-species discrimination according to reaction between antigen-antisera by serotyping technique and patterns generated by RAPD bands. Two screened RAPD primers demonstrating potentially useful banding patterns were selected and examined against L monocytogenes isolates. Positive isolates were evaluated for their susceptibility to eight commonly used antibiotic agents by using disc diffusion assay. L monocytogenes was detected in 8.57% of collected food samples which 33.3%, 25% and 13.3% were detected in burger, minced meat and sausage samples respectively. The highest resistances (100%) of L monocytogenes isolates were demonstrated against ampicillin and penicillin G antibiotics, whereas high susceptibility was showed toward streptomycin (100%). The molecular approaches used in this study provide highly sensitive and specific results which were very easy and fast to perform. These findings also suggested that the contamination of L monocytogenes in foods is relatively low. However, it highlighted the emergence of antibiotics multi-resistant Listeria in the present environment.